Mechanical behaviours of hydrated cement treated crushed rock base as a road base material in Western Australia - Jitsangiam, Peerapong; Nikraz, Hamid (Taylor & Francis, 2009)
Hydrated cement treated crushed rock base (HCTCRB) is widely used as a base course material for Western Australian roads. In order to be able to use this material effectively, its shear strength, resilient modulus and permanent deformation characteristics should be investigated and clearly understood. This study aimed to carry out the results of implement laboratory testing, which was to assess the mechanical characteristics of HCTCRB. Our findings show that HCTCRB can be characterised as the cohesive granular material that has a cohesion (c) of 177 kPa and an internal friction angle of 42°. The resilient modulus characteristics can be modelled using the Uzan model. The permanent deformation characteristics can be modelled using the Sweere, G.T.H.'s model. These models are based on the test results following the Austroads – APRG 00/33 test standard.